2021
DOI: 10.1111/jgh.15372
|View full text |Cite
|
Sign up to set email alerts
|

Advancing care for acute gastrointestinal bleeding using artificial intelligence

Abstract: The future of gastrointestinal bleeding will include the integration of machine learning algorithms to enhance clinician risk assessment and decision making. Machine learning algorithms have shown promise in outperforming existing clinical risk scores for both upper and lower gastrointestinal bleeding but have not been validated in any prospective clinical trials. The adoption of electronic health records provides an exciting opportunity to deploy risk prediction tools in real time and also to expand the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…ANVUGIB is mainly caused by diseases of the upper digestive tract and biliary and pancreatic diseases. Peptic ulcers, upper gastrointestinal tumor, and acute gastric mucosal lesions were the most common [21]. This study showed that the most common causes of acute nonvaricose upper gastrointestinal bleeding were peptic ulcer, acute gastric mucosal lesion, and upper gastrointestinal tumor, and other causes were esophagocardiac mucosal tear syndrome [22].…”
Section: Discussionmentioning
confidence: 69%
“…ANVUGIB is mainly caused by diseases of the upper digestive tract and biliary and pancreatic diseases. Peptic ulcers, upper gastrointestinal tumor, and acute gastric mucosal lesions were the most common [21]. This study showed that the most common causes of acute nonvaricose upper gastrointestinal bleeding were peptic ulcer, acute gastric mucosal lesion, and upper gastrointestinal tumor, and other causes were esophagocardiac mucosal tear syndrome [22].…”
Section: Discussionmentioning
confidence: 69%
“…A prospective study of 170 patients with LGIB comparing a variety of pre-endoscopic scoring systems demonstrated that no score had an excellent predictive ability across all important outcomes in LGIB, including severe bleeding, need for PRBC transfusion, inhospital recurrent bleeding, and need for endoscopic intervention (52). A few machine learning algorithms have been studied in small LGIB cohorts to accurately predict specific outcomes such as need for surgery and rebleeding (53,54); however, these algorithms have not been externally validated nor are they used clinically (55).…”
Section: Key Conceptsmentioning
confidence: 99%
“…The effectiveness of detecting higher-risk individuals is unknown, although it has lately been investigated by anticipating in-hospital death in individuals brought to the intensive care unit with severe GIB. Machine learning technologies provide some benefits over medical risk ratings, such as the capacity to enhance over time and be retrained using information that reflects local epidemiology and illness trends [ 2 ].…”
Section: Introductionmentioning
confidence: 99%